Klondike Annie Based on a Play by Mae West - Walsh, Raoul; Clemens, George T.; West, Mae; MacLaglen, Victor; Reed, Phillip (Universal Pictures, 2005)
The tale is set in the naughty nineties, a favourite period for West, in the Yukon Valley, where bad girl West flees after murdering her lover, and takes the place of a recently dead missionary. She is then quite a shock to the Alaskan community, as she staits to give sermons from the pulpit. This so incensed the ontemporary critics that one of them declared that the film was "unfit to be shown", and the censors cut out some of the jucier scenes. Apparently, ridiculing religion just wasn't on. The new element that West introduced here went largely unnoticed by the audiences of the day: compared with her earlier characters, the West of "Klondike Annie" seems so much more intelligent, and serious with it. West had introduced some social comment, and given her character a conscience: but the songs and gags are present in just a great a number as before. Her co-star is craggy yet lovable Victor McLaglen, in a thankless role unworthy of his talents - it really is West's show all the way - but his presence adds to the comedy. [www.eufs.org.uk]